Factors influencing the utilization of research findings by health policy-makers in a developing country: the selection of Mali's essential medicines - Fretheim Atle; Albert Michael A; Maïga Diadié (BMC, 2007)
Abstract Background Research findings are increasingly being recognized as an important input in the formation of health policy. There is concern that research findings are not being utilized by health policy-makers to the extent that they could be. The factors influencing the utilization of various types of research by health policy-makers are beginning to emerge in the literature, however there is still little known about these factors in developing countries. The object of this study was to explore these factors by examining the policy-making process for a pharmaceutical policy common in developing countries; an essential medicines list. Methods A study of the selection and updating of Mali's national essential medicines list was undertaken using qualitative methods. In-depth semi-structured interviews and a natural group discussion were held with national policy-makers, most specifically members of the national commission that selects and updates the country's list. The resulting text was analyzed using a phenomenological approach. A document analysis was also performed. Results Several factors emerged from the textual data that appear to be influencing the utilization of health research findings for these policy-makers. These factors include: access to information, relevance of the research, use of research perceived as a time consuming process, trust in the research, authority of those who presented their view, competency in research methods, priority of research in the policy process, and accountability. Conclusion Improving the transfer of research to policy will require effort on the part of researchers, policy-makers, and third parties. This will include: collaboration between researchers and policy-makers, increased production and dissemination of relevant and useful research, and continued and improved technical support from networks and multi-national organizations. Policy-makers from developing countries will then be better equipped to make informed decisions concerning their health policy issues.